Hospitalised burns in children up to 16 years old: A 10‐year population‐based study in Australia. (12th December 2018) - Seah, Rebecca; Holland, Andrew JA; Curtis, Kate; Mitchell, Rebecca
Abstract : Aim: Globally, burns remain a significant public health issue that disproportionately affect young children. The current study examines the 10‐year epidemiological profile of burn hospitalisations, hospital treatment cost and health outcomes by age group for children ≤16 years in Australia. Methods: National, population‐based, linked hospital and mortality data from 1 July 2002 to 30 June 2012 were used to identify burn‐related hospitalisations. Age‐standardised hospitalisation rates and hospital treatment costs were estimated. Results: There were 25 098 children aged ≤16 years hospitalised after sustaining a burn. The age‐standardised hospitalisation rate was 54.4 per 100 000 (95% confidence interval (CI): 53.7–55.1). Children aged 1–5 years had the highest burn hospitalisation rate (105.6 per 100 000; 95% CI: 103.8–107.3). The burn hospitalisation rate of infants <1 year declined by 3.1% per annum (95% CI: −4.84, −1.37, P  < 0.001). Contact with heat and other substances, hot drinks, food, fats and cooking oils was the most common burn mechanism, and the home was the most common place of occurrence for children ≤10 years. Exposure to the ignition of highly flammable material was the most common burn mechanism for children aged 11–16 years. There were 7260 hospital readmissions within 28 days and 11 deaths within 30 days of the index burn hospitalisation. Total hospital treatment costs were estimated at $168 million. Conclusions: Childhood burns continue to account for a large proportion of hospitalised morbidity. To assist in reducing burn hospitalisations, the development, implementation and resourcing of national multi‐sectorial childhood injury prevention is needed in Australia.